Successful eradication of an invasive alien Pallas’s squirrel (Callosciurus erythraeus Pallas 1779) population in the Netherlands with support of the local community - La Haye, Maurice J. J.; Janssen, René; Adriaens, Tim; Huysentruyt, Frank; Voskamp, Paul J.; Lammers, Wiebe; Dijkstra, Vilmar (Frontiers in Ecology and Evolution, 2023)
The Pallas’s squirrel (Callosciurus erythraeus) is an invasive alien species in several countries in Europe, but also in Argentina and Japan. The species is a threat to indigenous squirrel species and difficult to eradicate. In 2008 a population of this species was discovered in the south of the Netherlands, close to the Belgian border. The range and number of Pallas’s squirrels in the area was determined using sightings of local citizens, foresters and an extensive inventory with hair tubes and camera traps. The population was successfully eradicated during an eradication campaign with several stages from 2011 till 2015. The population appeared to be larger than expected. In total, 249 individuals were trapped in an area as large as 50 km2. Trapped squirrels were not killed, but sterilized and rehomed in animal parks across Europe. The eradication campaign was successful due to the cooperation and support of the general public, who were informed by flyers, lectures and several appeals in local media and on social media platforms. Both helped in getting support of the general public, but sterilization and rehoming must be properly supervised. The total costs of eradication summed up to at least €330,000. No Pallas’s squirrels were reported after October 2015, however sightings of ‘dark colored’ squirrels from the area are still reported by the general public and verified by an expert of the Dutch Mammal Society until today.